A Study of Impact of Wheel and Track Wear on Train Swaying - Luqman Hakimi Taufiq,; Nurul Farhanah binti Muarat,; Amir bin Nordin, (Progress in Engineering Application and Technology, 2025)
Train swaying is a critical phenomenon affecting the safety, stability, and comfort of railway operations. This study investigated the influence of wheel and track wear on the severity of train swaying, focusing on the complex interactions between vehicle dynamics, rolling stock parameters, and environmental conditions. Utilizing a combination of literature analysis, expert consultation, and field measurements, including the use of motion tracking sensors, this research identified key variables contributing to lateral train instability. Results demonstrated that wheel flange wear and improper suspension characteristics were found to exhibit inconsistent swaying motion. The study highlighted the importance of coordinated maintenance strategies between track and rolling stock operators. The findings provided insights that can help improve ride quality, enhance passenger safety, and support the development of more resilient railway infrastructure.